Antioxidative defense mechanism against lead-induced phytotoxicity in Fagopyrum kashmirianum. (February 2019) - Hakeem, Khalid Rehman; Alharby, Hesham F.; Rehman, Reiazul
Abstract: The effect of lead (Pb)-induced oxidative stress was investigated in Fagopyrum kashmirianum . The seedlings absorbed the Pb readily by showing time (15 and 30 days) and concentration (0, 100, 200 and 300 μM) dependent effects. Pb caused reduction in both root and shoot lengths but its accumulation was more in roots (22.32 mg g −1 DW) than shoots (8.86 mg g −1 DW) at the highest concentration (300 μM) resulting in translocation factor (TF) < 1 at all concentrations. Thus the uptake and translocation of Pb between roots and shoots showed a positive correlation indicating the plant as root accumulator. Amongst the photosynthetic pigments, chlorophyll content showed a decline while the carotenoid and anthocyanin levels were elevated. The fresh mass and biomass showed a non-significant decrease at both the sampling times. The osmolyte and antioxidative enzymes (SOD, CAT, APX. POD, GR and GST) were positively correlated with Pb treatments except proline and CAT, which showed decline in 30-day-old plants. The alleviation of Pb-stress is an indication for existence of strong detoxification mechanism in F. kashmirianum, which suggest that it could be cultivated in Pb-contaminated soils. Highlights: F. kashmirianum has the ability to tolerate Pb toxicity and hyperaccumulate a significant Pb content in roots. The levels of antioxidative enzymes and osmolytes were significantly increased in F. kashmirianum under Pb stress. MDA content and photosynthetic pigments were enhanced significantly corresponding to the increase in Pb stress applied.